Design, development and performance of solar dryer for pineapple (Ananas comosus (L.) Merr.), mamey (Mammea americana L.) and banana (Musa paradisiaca L.) fruit drying (2018)
The aim of the present research was to know the shelf life of dehydrated tropical fruits based on an indirect type solar dryer, which was designed and developed under the conditions of Calceta, Bolívar canton of Manabí province, Ecuador. Due to the banana fruit physical and chemical characteristics exhibited during the process of dehydration by radiation, satisfactory results were obtained, superior to those obtained in fruits of mamey and pineapple. For example, moisture in banana with 80.22% dropped to 10.35%; in relation to protein ratio, which had achieved an increasing from 1.27% in its fresh state to 2.18% and in fiber contents from 0.88% in its fresh state to 2.41%. The microbiological analyzes determined the shelf life of the estimated products at 106, 109 and 174 days, respectively, for mamey, banana and pineapple fruits. Conversely, the attributes measured according to the scale of the sensory evaluation, the average of the treatments and their properties, such as sweetness, appearance, color and taste, can be demonstrated that the banana fruit considers better attributes as color with 4.38; sweet 4.58; aspect 4.68; and taste 4.75. In banana fruit, the R2 statistic indicates 56.339% of the variability in DM PL. The correlation coefficient is equal to 0.750593, indicating a moderately strong relationship among the evaluated variables.